Guest editorial: exploring happiness in the workplace as an essential theme for developing managers post-pandemic - Ravina-Ripoll, Rafael; Galván Vela, Esthela; Popescu, Cristina Raluca Gh.; Ahumada-Tello, Eduardo (Emerald Publishing Limited, 2023)
As recovery from the global pandemic takes shape, there are signs of a desire to rethink how our organisations manage, whether notions of building back better or fairer and more sustainable approaches resonate with the UN's long-established Sustainable Development Goals (SDGs). In this sense, happiness and well-being are at the heart of the UN's 2030 agenda to achieve the SDGs. It challenges organisations to find new ways of managing for sustainable and competitive advantage through the happiness of their employees at work (Ravina-Ripoll et al., 2021). This issue takes on particular relevance during the pandemic, as at this time, an essential academic and professional debate arises on the need to implement management models that revolve around the happiness at work of their human capital (Elías Zambrano et al., 2021). RESUMEN A medida que la recuperación de la pandemia mundial va tomando forma, hay signos de un deseo de repensar cómo se gestionan nuestras organizaciones, si las nociones de reconstruir mejor o de enfoques más justos y sostenibles resuenan con los Objetivos de Desarrollo Sostenible (ODS) establecidos desde hace mucho tiempo por las Naciones Unidas. En este sentido, la felicidad y el bienestar están en el centro de la agenda 2030 de la ONU para alcanzar los ODS. Desafía a las organizaciones a encontrar nuevas formas de gestionar una ventaja competitiva y sostenible a través de la felicidad de sus empleados en el trabajo (Ravina-Ripoll et al., 2021). Este tema cobra especial relevancia durante la pandemia, pues en estos momentos surge un debate académico y profesional imprescindible sobre la necesidad de implementar modelos de gestión que giren en torno a la felicidad en el trabajo de su capital humano (Elías Zambrano et al., 2021).
Journal of management development de emerald insight.
Keywords: Post-pandemic; Workplace; Managers; Campus Tijuana